UJI PEMBUATAN BIOGAS DARI KOTORAN GAJAH DENGAN VARIASI PENAMBAHAN URINE GAJAH DAN AIR - Hardyanti, Nurandani; Sutrisno, Endro (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Biogas was a gas produced from biological activities in anaerobic fermentation processes and as  a renewable  energy.  This  research  was  to  find  out  the  effect  between  elephant  manure, elephant urine, water and starter to reduce biogas production and calorie value. This research is divided  into  three groups  based  on  the  raw  material,  i.e.,  elephant  manure,  elephant  urine, water  and  starter  as independent  variabels.  Observation  is  consisted  of  biogas  production volume and calorie value. This result showed that in 21 days, elephant manure mixtured with elephant urine with ratios of 1:2  was the best material to produce biogas, that was 60,800 ml of biogas and 5345.39 cal/liters of calorie value.